Analysis of annoyance caused by infrasound and low-frequency noise during mental work - Anna KACZMARSKA; Anna ŁUCZAK (Archives of Acoustics)
This paper presents the results of low-frequency noise (LFN) annoyance tests in laboratory conditions on a model workstation conceptual mental work. Group of volunteers: 60 persons (30 women and 30 men) participated in the experiment consisting in completing psychological tests in three different acoustic conditions. The tests results have shown significant differences in subjective assessment of noise annoyance depending on the gender and reactivity level of surveyed persons.